Management of Recurrent Anterior Uveitis in Spondyloarthritis: A Case Report: Poster Presentation - Case Report - Resident - nadida nurfadhila; Patriotika Muslima; Elfa Ali Idrus; Arief Akhdestira Mustaram; Angga Fajriansyah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Non-infectious anterior uveitis is caused by underlying diseases, one of which is spondyloarthritis. Spondyloarthritis is a part of chronic rheumatic disease. The main goals of uveitis therapy are to prevent blindness, permanent organ damage, and recurrence. Case Illustration : A 19-years old woman came to Cicendo Eye Hospital with blurry vision for one week. The complaint was accompanied by redness, photosensitivity, and pain in her right eye. She had similar complaints in her right eye one month ago and in her left eye one year ago. She also had a history of morning stiffness in her knee joint and lower back pain. For those symptoms, the rheumatologist diagnosed her with spondyloarthritis. The uncorrected visual acuity examination for both eyes were 0,16. Anterior segment examination on right eye were blepharospasm, ciliary injection, corneal oedema, flare and cells while the left eye within normal limit. She was diagnosed with anterior uveitis and was treated with topical corticosteroid, oral corticosteroid, and immunomodulator. Knowing the treatment was not responding, the rheumatologist added biologic agents to the therapy. As a result, the patient’s conditions improved. Discussion : Topical steroid therapy was used as the first line of treatment, but for the recurrence of anterior uveitis, systemic medication, including biologic agents, is needed. Conclusion : Multidiscipline and stepwise approach to treat anterior uveitis with underlying disease is necessary.